IMPROVING THE QUALITY OF STUDENT ACHIEVEMENT USING A DIFFERENTIATED LEARNING APPROACH - Rustemova, A.N. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
This article uses differentiated learning technology to teach each student to develop a range of skills and to select, compare, analyze, communicate, interpret and articulate the results of processes and phenomena. A differentiated teaching method is used based on results and objectives and outcomes.Due to this, students will be able to work in a collaborative environment and develop a love of the simple and the complex, work independently, developing research skills, focusing on the correct analysis of information.
Keywords: differentiated education; differentiation; English language; English lesson; technology; educational environment